Determinant of Sukuk Issuance in Indonesia From Information Asymmetry Perspective (2013-2022) - Imaroh Mawaddah (UniSadhuGuna Business School, 2023)
Previous research found that sukuk is more exposed to information asymmetry problems, especially adverse selection, than bond. Indonesia as the third largest country for sukuk market falls below its peers in terms of governance. It means the information asymmetry in Indonesia is relatively higher which could reduce market effectiveness. So to improve sukuk market in Indonesia, studying the implication of information asymmetry and how it affects the capital structure decision is important. This study try to explain the issuance of sukuk in Indonesia 2013-2022 from information asymmetry perspective. This study uses secondary data from 2013-2022 and would be done by using logistic regression to conclude if the variables representing adverse selection and moral hazard affect the decision of sukuk issuance. Our regression found evidence of adverse selection in Indonesia sukuk market but did not find moral hazard problem. The result supports previous research that concludes that sukuk structuration leads firms with higher financial distress and a lower reputation to enter the market. The result could help investor to understand sukuk market and review their risk management procedure. It could also become additional material for government to design a suitable regulatory environment for a more govern sukuk market that would improve the development of sukuk market.